Disparity in Bankruptcy Rulings: Rethinking the Principle of Simple Proof in the Indonesian Commercial Judiciary - Abrielmovich, Biyandra Timothee; Joesoef, Iwan Erar (Universitas Islam Negeri Alauddin Makassar, 2025)
This study investigates the principle of simple proof in Indonesian bankruptcy law, as stipulated in Article 8(4) of Law No. 37 of 2004, and its inconsistent application in judicial practice. The purpose of the research is to critically examine the disparity in court decisions regarding the interpretation of